Duração da espermatogênese e transplante xenogênico de células germinativas de jundiá (Rhamdia quelen) - Mariana de Araújo da Silva (2016)
Due to its rapid growth, good adaptability to different environmental conditions and economic importance, the jundiá (Rhamdia quelen) represents an excellent experimental model to investigate the structure and function of the testes and even reproductive biotechnologies in teleosts. Spermatogonial transplantation is one of these biotechnological approaches and consists of removing stem cells from the testicle of a donor animal and transferring them to the testicle of a recipient animal, where these cells will develop and form mature sperm with genetic characteristics of the donor. In teleost fish, this technique was successfully developed in our laboratory, using nilotic tilapia (Oreochromis niloticus) as an experimental model for allogeneic transplantation. In the present study, we investigated the feasibility of xenogeneic transplantation using nilotic tilapia as a recipient model for the development of jundiá stem spermatogonia. After transplantation, we observed that the somatic microenvironment of the tilapianilotic gonad is capable of allowing the colonization, proliferation and differentiation of transplanted jundiá spermatogonial stem cells. Thus, this study was a pioneer in demonstrating sperm production after xenogeneic transplantation between species belonging to different taxonomic orders, indicating that, unlike mammals, fish testes show great phylogenetic plasticity in relation to the factors necessary for the development of exogenous spermatogenesis. Furthermore, seeking to better understand the reproductive characteristics of jundiá, we carried out experiments to describe the morphology of its germ cells, as well as estimate the duration of spermatogenesis in this species. In this way, similar to other fish species, we demonstrate that a drastic reduction in the nuclear volume of germ cells occurs during spermatogenesis. This volumetric decrease is particularly observed in the spermatogonial phase (from undifferentiated spermatogonia to type B spermatogonia), as well as from the end of the meiotic phases to the end of the spermiogenic phase (between diplotenes and final spermatids). In another aspect of this investigation, through immunohistochemical analyzes of jundiá testis, carried out after injection of BrdU at different time intervals, we observed that the combined duration of the meiotic and spermiogenic phases in this species was very short, requiring around 7 days for the differentiation of early primary spermatocytes into spermatozoa. However, although this duration is similar to that found for nilotic tilapia kept at the same temperature (30oC), we observed that, compared to transplantation between tilapia, a longer period of time is required for the production of exogenous spermatozoa after xenogeneic jundiá transplantation. for tilapia. In this sense, more studies are necessary to understand the physiological aspects involved in the adaptation and colonization of catfish stem spermatogonia in the testicular environment (spermatogonial niche) of nilotic tilapia after transplantation. Finally, in addition to better understanding the aspects relating to the testicular physiology and reproductive biology of jundiás, the studies developed by us here provide a very promising scenario in relation to the use of nilotic tilapia to produce sperm from other teleost species that are threatened. of extinction and/or that have commercial interest in aquaculture.